Ontologia e genealogia delle macchine: un sunto - Russo, Nicola (Mechane, 2021)
Our essay will depict a unitary framework that relates art and technique, and it will display the impact of the ontology of machines on the anthropology of technique. In contrast to the efficient cause paradigm as the core of machinery, we focus on teleological concerns to establish a multilayered approach. Therefore, we aim to avert the danger of deriving a depleted conception of man and nature from an equally depleted understanding of the machine.